Re-Islamization of Land Law in Global Context: An Approach to Fight Ecological Scarcity - Arif Al Anang; Noorhidayah; Mustafa; Nor Ismah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This research departs from concerns about an environmental crisis that encompasses deforestation, land-use change, habitat loss, land grabbing, water contamination, and soil degradation that we have faced. Meanwhile, the urgency of an Islamic response to fight those conditions should be more than simple actions like a religious lecture, Friday sermon, or green fatwa for around 1.9 billion Muslim communities around the world. Therefore, this study aims to critically analyze the Sharia contribution today to improve environmental protection by re-Islamization of forest and land law in modern ways, ultimately, to prevent the development and utilization of land and forest resources from continuing to fall into the vicious circle of the past. As an Islamic environmental law research, this study used a multi-disciplinary approach, including historical approach, empirical approach, and conceptual approach; it also used a literature review method to synthesize research findings. This paper found that re-Islamized forests and land law could be an ongoing debate due to the differences of national and local legal characteristics that also depend on sharia position if it is an unequivocal discourse. Moreover, accommodating Sharia as an integral part of the state law shown a uniqueness and the flexibilities of Islamic doctrine and an affirmation of Muslim optimism to their faith of course a real contribution to involve in ecological right movement. On the other hand, considering the re-Islamization of forests and land law is an alternative source to enforce the ecological behaviours of the Muslim community to more pro-environment.